Blockage Types and Status Evaluation of Drainage System in Highway Tunnels in Guangdong Province - LI Kejian; LIU Xiabing; WENG Jianhong; ZHOU Yu (Renmin Zhujiang)
In order to evaluate the blockage status of the drainage system in operational highway tunnels,this paper summarized the types of problems and blockage materials in highway tunnel drainage systems and proposed an evaluation method for blockage status based on investigations of several highway tunnels in Guangdong Province.The results primarily indicated the following:① The water leakage problems in tunnels were closely related to seasonal rainfall over time and were spatially connected to the distribution of unfavorable geological conditions such as karst.and the decline of drainage function caused by drainage system siltation was an important cause of tunnel water damage.② The types of blockage materials in the highway tunnel drainage system included silt,sand and gravel,concrete blocks or foreign matter,and crystallization or scale deposits.The proposed evaluation indicators for blockage status were as follows:filling degree,flow status,turbidity degree,and accumulation degree.③ Based on the priority division of evaluation indicators for blockage status, a blockage status evaluation method of highway tunnel drainage systems was proposed,and this method has been successfully applied to the drainage system remediation project of the Xinwu Tunnel.The research results can provide reference for the operation and maintenance of highway tunnel drainage systems.